Intrapulmonary artery septation for unilateral absence of the pulmonary artery. (May 2022) - Koizumi, Junichi; Iwase, Tomoyuki; Tsuji, Shigeto; Goto, Takuya; Oyama, Kotaro; Kin, Hajime
We describe a seven-month-old boy with tetralogy of Fallot and an absent left pulmonary artery. Due to the diminutive size of the left pulmonary artery, we performed a native tissue left pulmonary artery reconstruction and intrapulmonary artery septation procedure with a left modified Blalock-Taussig shunt. After confirming left pulmonary artery growth, the patient underwent tetralogy of Fallot repair, removal of septation patch, and division of the Blalock-Taussig shunt. Nine months post-surgery, we confirmed his balanced lung perfusion (R/L ratio 6:4). The intrapulmonary artery septation procedure would be suitable for both the resuscitation and reconstruction of the hypoplastic absent pulmonary artery.